Competitive politics, simplified heuristics, and preferences for public goods - Felix Schläpfer; Marcel Schmitt; Anna Roschewitz (University of Zurich, Socioeconomic Institute, 2007)
This paper examines the role of simplified heuristics in the formation of preferences for public goods. Political scientists have suggested that voters use simplified heuristics based on the positions of familiar parties to infer how a proposed policy will affect them and to cast a vote in line with their interests and values. Here, we use a two-stage field-survey experiment to investigate how knowledge of party positions affects policy choices. We followed standard procedures in developing an attribute-based choice experiment on alternative land-use policies in Switzerland. In contrast to the usual formulation, however, the hypothetical costs of the proposed policies were formulated as a percentage change in taxes. The benefit of this formulation relative to the usual absolute money amounts is that the credibility of the (hypothetical) costs for respondents does not depend on respondent income. Furthermore, the formulation allowed us to solicit party positions on the proposed policies. Six out of eight contacted parties provided their positions. We then conducted a split-sample mail survey where we included a table of the party positions with a subsample of the questionnaires. We report six main experimental results. (1) The response rate of the survey was unaffected by the party positions. (2) The proportion of no-choice answers was decreased by forty percent relative to the control. (3) The party information significantly affected the choices directly and in interaction with respondents' general attitudes towards public spending for nature and landscape conservation and thus affected the way how individuals mapped from general attitudes to preferences for specific policies. (4) The information interacted with educational level in only eight out of forty choice sets, suggesting that even the more educated relied on simplified heuristics. (5) Respondents who knew the party positions were more sensitive to the tax attribute. (6) For respondents with medium and higher tax bills, the resulting willingness-to-pay estimates were decreased by a factor of two to ten relative to the control. These findings suggest that the party information helped the respondents to articulate more consistent preferences than in the treatment without the party information.
Keywords: D61; D70; D81; Q26; Q28; Q51; 330; agriculture; bounded rationality; choice experiment; contingent valuation; landscape; heuristics; information; preference formation; public goods; voting; Öffentliche Güter; Präferenztheorie; Willingness to pay; Beschränkte Rationalität; Test; Theorie